Design and Evaluation of Digidongeng: An Interactive Digital Storybook for Early Childhood Sexual Education - Naura Shafwah; Asep Kurnia Jayadinata; Risty Justicia; Lily Muliana Mustafa; Dhea Ardiyanti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Cases of sexual violence against young children continue to rise, underscoring the need for developmentally appropriate and engaging early childhood sexual education. This study aimed to (1) analyze teachers’ needs for sexual education learning media and (2) design, develop, and conduct an initial evaluation of Digidongeng, an interactive digital storybook for children aged 5–6 years. Using a Design and Development approach with the ADDIE model, the analysis stage involved interviews with two early childhood teachers to identify content priorities, preferred media features, and implementation concerns. Based on these findings, Digidongeng was designed and developed using Book Creator with multimedia elements (narration, visuals, and interactive buttons). The product was validated by two experts (content and media) using a 4-point rubric covering presentation, relevance, usability, and safety. A limited classroom trial was then conducted with 20 kindergarten children; children’s engagement, ability to operate the media, and observable comprehension were documented using observation sheets. Expert validation indicated that Digidongeng was highly feasible (98.07% for both content and media validation). In the field trial, overall feasibility reached 93.5% (374/400), with children showing high interaction and sustained interest, and teachers reporting that guided facilitation supported children’s participation. Digidongeng demonstrates strong initial feasibility and acceptability as an interactive, child-friendly medium to support early childhood sexual education. Further research should examine learning outcomes with stronger evaluation designs and broader implementation across diverse settings.